Sistem Monitoring Penyiraman Bibit Tanaman Jeruk Siam Dengan Menggunakan Modul Nodemcu ESP 8266 Dan Sensor Kelembaban Tanah Berbasis IOT - Anggraeni, Feni; Rofiq, Muhammad (Institut Tekonologi dan Binisi Asia Malang, 2024)
The process of watering on the seeds of the conjoined orange plant can be monitored through an android smartphone. Which aims to simplify the process of watering that is done remotely or close distance and to monitor the moisture value in the soil of the seeds of the conjoined orange plant. The monitoring system for planting conjoined citrus seedlings using the nodemcu esp8266 module and iot-based soil moisture sensor is a way that can monitor the soil moisture value in the ground of the conjoined citrus seedlings. By using the Soil Moisture Sensor yl-69 as an input or detecting the value that is planted in the soil. The Nodemcu ESP8266 module is a microcontroller and is forwarded to the Relay module which will later control the valve in the Solenoid Water Valve in the process of watering. The results of the humidity value and also the status of the solenoid water valve pump will be sent through the internet network to the Firebase Realtime database and displayed on an Android Smartphone that has an application installed in it, an application created using the MIT App Inventor application. From the results of testing the overall tool system shows that the system is able to provide information on soil moisture values and keep soil moisture stable. And can monitor and detect 70% - 90% humidity from 10 times the tests carried out using an android smartphone at a distance and close well in accordance with the commands given.